Hubungan Motivasi Berprestasi dan Komunikasi Interpersonal dengan Keefektifan Pengelolaan Kelas Guru-guru IPA SMP - Eddy Rompas (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2006)
The aim of this survey is to investigate the relationship between achievement motivation and interpersonal communication competence and the effectiveness of classroom management. Using multi-state sampling technique, this study involved 42 teacher respondents. Questionnaires were distributed, which were then statistically analyzed using regression. It was revealed that achievement motivation and interpersonal communication competence, both individually and aggregately, contribute to the effectiveness of classroom management.